Peran Zakat, Infaq, Shadaqah dan Wakaf dalam Memberdayakan Ekonomi Ummat - Rijal Allamah; Sri Sudiarti; Julfan Saputra (Al-Sharf: Jurnal Ekonomi Islam, 2021)
The problem of poverty is always interesting to study because it is a serious problem involving the human dimension. Poverty remains a problem that cannot be considered easy to find a solution for because it has existed for a long time and has become a living reality in society. To help the poor, many financial institutions, especially Islamic financial institutions, such as amil zakat institutions provide assistance in the form of ZISWAF funds (Zakat, Infak, Shadaqah, Waqf). With regard to ziswaf funds, especially zakat funds, amil zakat institutions not only distribute consumptive zakat but also productive zakat or commonly referred to as productive zakat.Keywords: Zakat, Infaq, Sadaqah and waqf